Hi all! Let me use an example to make this clear. There is a car travelling directly toward a man at 10m/s. The car is pressing down its horn, producing a frequency of 100hz. The speed of sound is 330 m/s. What frequency does the man hear? Ok, so we can use the equation: f_observer=( (v+v_o)/(v-v_s ) ) * f_source Where v=330, v_o=0 & v_s = 10 Thus f_observer = 103.125 But, if the car was still and the observer moved toward the car at 10m/s we could say: f_observer=( (v+v_o)/(v-v_s ) ) * f_source Where v=330, v_o=10, v_s =0 thus f_observer = 103.0303.... 103.0303 does not equal 103.125. Why is there a difference, surely these two things could be the same.